Diagnosing students' biology misconceptions using an android-based four-tier multiple choice test - Nukhbatul Bidayati Haka; Mailinda Suri; Supriyadi Supriyadi; Akbar Handoko; Mivtha Citra Ningrum (Universitas Negeri Padang, 2023)
This research aims to develop an android based Four-tier multiple choice test instrumen to diagnose student’s misconceptions on appropriate and interesting biology subjects. This is Research and Development (R&D), which uses Borg and Gall design, 7 stages. In this study, data use from media experts, question/ material experts, linguists, educators’ responses, student responses, and data from students’ misconceptions. Based on the results of the research that the android based Four-tier multiple choice test instrumen to diagnose the misconceptions of class XI students in biology subjects using the Borg and Gall design model up to 7 stages which include, research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, and operational product revision. After conducting tests on the Four-ter multiple choice test instrumen to diagnose students’ misconceptions in biology subjects, an assessment with very feasible and interesting criteria has been obtained.